Socio-economic determinants of infant and child mortality in Haiti - Gordon, Ronald M. (2009)
Proposes the hypothesis that maternal education has a positive influence on the reduction of childhood mortality in Haiti after controlling for place of residence, income measured by a proxy variable and sanitation measured by access to piped water.